1994
DOI: 10.1128/mcb.14.4.2429
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic activation of the Lck protein accompanies translocation of the LCK gene in the human HSB2 T-cell leukemia.

Abstract: The tyrosine protein kinase p56ick transduces signals important for antigen-induced T-cell The lymphocyte-specific tyrosine protein kinase, p561ck, is expressed predominantly in T cells (13,30,53), where it is physically associated with the T-cell transmembrane proteins CD4 and CD8 (43,45,52). During T-cell activation, CD4 and CD8 bind to the major histocompatibility complex glycoprotein (class II or class I, respectively) on an antigen-presenting cell, bringing p56ick in close physical proximity to the T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 46 publications
3
36
0
Order By: Relevance
“…We electroporated 9 T-ALL cell lines (ALL-SIL, HSB-2, HPB-ALL, MOLT-14, KE-37, SUP-T1, DND-41, P12-ichikawa, and TALL-1) with our siRNA library, and searched for siRNAs that significantly affected proliferation and survival of the cells. As expected, we identified ABL1 (NUP214-ABL1) as an essential kinase in ALL-SIL cells, 3 and LCK as an essential kinase in HSB-2 cells, 5 2 cell lines known to depend on these oncogenic kinases (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). In addition, we identified tyrosine kinases that affected the proliferation and survival of several other T-ALL cell lines, the strongest hit being JAK1 in DND-41 cells (supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…We electroporated 9 T-ALL cell lines (ALL-SIL, HSB-2, HPB-ALL, MOLT-14, KE-37, SUP-T1, DND-41, P12-ichikawa, and TALL-1) with our siRNA library, and searched for siRNAs that significantly affected proliferation and survival of the cells. As expected, we identified ABL1 (NUP214-ABL1) as an essential kinase in ALL-SIL cells, 3 and LCK as an essential kinase in HSB-2 cells, 5 2 cell lines known to depend on these oncogenic kinases (supplemental Figure 1, available on the Blood Web site; see the Supplemental Materials link at the top of the online article). In addition, we identified tyrosine kinases that affected the proliferation and survival of several other T-ALL cell lines, the strongest hit being JAK1 in DND-41 cells (supplemental Figure 2).…”
Section: Resultsmentioning
confidence: 85%
“…Notably, these loss-of-function mutations all occurred together with activating mutations in pathways that are negatively regulated by CD45 (supplemental Table 1): CD45 R751* with a JAK1 Y652H gain-of-function mutant in patient TLE-28, 23 CD45 W764* with an activating IL-7R insertion in DND-41, and CD45 G863R with activating LCK mutations in HSB-2. 5,24 Furthermore, our data indicate that loss of CD45 renders the JAK/STAT signaling pathway more susceptible to activation, either by cytokines or by oncogenic proteins, and can affect cancer cell proliferation. Although CD45-inactivating mutations appear to be quite rare, it has been reported that CD45 expression is extremely low or undetectable in 3.7% of pediatric T-ALL and 12.9% of pediatric B-cell precursor ALL patients, 25 suggesting that additional mechanisms may exist for the inactivation of CD45.…”
Section: Cd45 Mutations In T-all 4477mentioning
confidence: 99%
See 1 more Smart Citation
“…Cells Culture and Transfection-The HSB-2 T cell line was maintained in RPMI 1640-glutamine (Invitrogen BLR) sup-plemented with 10% fetal bovine serum and 2.4 mM glutamine at cell numbers between 1 and 4 Ï« 10 6 cells/ml (28). Transfections of HSB-2 cells with DNA or siRNA were carried out as previously described (20).…”
Section: Protein Expression and Purification-escherichia Coli Cd41(dementioning
confidence: 99%
“…In humans, the lck gene is located at a site of frequent chromosomal abnormalities associated with lymphomas (4). Aberrant Lck expression and kinase activity have also been implicated in the pathogenesis of both lymphoid and nonlymphoid malignancies (5,6). Like other Src family members, Lck kinase activity is negatively regulated by phosphorylation of a highly conserved tyrosine (Tyr 505 ) located near the carboxyl terminus of the protein (7).…”
Section: Introductionmentioning
confidence: 99%